DEKONSTRUKSI PENAFSIRAN AYAT-AYAT AL-QUR’AN TENTANG WARISAN PEREMPUAN MENUJU KEADILAN GENDER - Wasiul Fikri (MUWAZAH : jurnal kajian gender, 2015)
This article will be reviewing how the interpretation holly Quran verse’s that seem biased. It is related to the gender in division of heritage to women with a sulk on the opinions from Indonesian’s Mufassir and Egypt’s Mufassir to reveal religious teaching which have been considered impartiality or less fair to women, especially in heritage area.